Use Of Jarimatics Method In Improving Primary School Students' Numerical Abilities - Imam Setiadi Putra (JPSL : Jurnal Pendidikan, Sosial dan Lingkungan, 2023)
This study aims to determine the contribution of using the Jarimatika method to improve students' numerical abilities. This research is an experimental quantitative research with a Quasi Experiment Design research design or quasi-research. This research was conducted in a school in Bima Regency, West Nusa Tenggara, Indonesia. The sample in the study consisted of 35 students who were all taken from the total population. Instruments in the study using multiple choice tests and essays. The data analysis technique used simple linear regression and t test. The results of this study indicate that the Paired-Sample T-test value is -12.887 and ttable is -1.753 with a significance level of 5%, so -26.88> -1.753 or -26.88 < - 1.753) which means that there can be a contribution using the Jarimatika method to improve students' numerical ability, with a large contribution of the Jarimatika method of 66.6%.